ACTION DE LA PAPAINA Y LA MEXICAINA SOBRE EL FIBRINOGENO - SANCHEZ MARROQUIN, AY; GAVARRON, FF (Instituto Nacional de Cardiología, CD MEXICO, DF, MEX, 1948)
The 3 known populations of Mexican blind characins of the genus Anoptichthys are studied and compared with Astyanax fasciatus mexicanus in order to determine the exact number and disposition of the suborbital bones Anoptichthys is redescr, incoiporating
AN ESC NAC CIENC BIOL
Keywords: ACTION, PAPAINA, MEXICAINA, FIBRINOGENO; CIENCIAS DE LA VIDA; BIOLOGIA CELULAR; CULTIVO CELULAR